Temperate-Tropical Variation in Breeding Synchrony and Extra-Pair Paternity Among New World Tachycineta Swallows - Ferretti, Valentina (2019)
Extra-pair paternity rates vary markedly across avian taxa, but patterns of variation in this trait have been obscured by a paucity of data on closely related species, especially those spanning broad environmental gradients. Here we compare variation in extra-pair paternity rates among fve species in the widespread swallow genus Tachycineta. Rates of extra-pair paternity vary widely in this group, ranging from 13 to 87% of nests having extra-pair young. The inter-specifc variation in extra-pair paternity within this small group of closely related swallows has a range equivalent to that found among all Hirundinidae and is close to the range of variation across all birds. Despite theory that predicts extrapair paternity rates to be explained by latitudinal variation in breeding synchrony our results show that extra-pair paternity rates in this genus do not closely track a latitudinal gradient, as predicted by studies of other life-history traits, and are not explained by diferences in breeding synchrony as previously suggested. The genetic mating systems of birds, described by the rates of extra-pair paternity, are connected to all other life-history traits through a complex network of trade-ofs with organismal (phylogenetic) and ecological (environmental) factors. Disentangling each of these interactions to understand latitudinal patterns in any given life-history trait remains a daunting task.